HUBUNGAN MITOS DAN DUKUNGAN SUAMI TERHADAP MINAT IBU DALAM PENGGUNAAN IMPLANT DI KELURAHAN KUNINGAN KECAMATAN SEMARANG UTARA - Willy Ananda Fridayani; Sutrisminah, Emi (Journal of Fundus, 2025)
Background: Indonesia's growing population has encouraged the government to implement family planning programs, particularly long-term contraceptive methods (MKJP) such as implants. However, use remains low, including in Kuningan Village (2.69%). This low interest is influenced by negative myths, such as the belief that implants can disappear, and a lack of husband support. This situation prompted research into the relationship between myths and husband support on interest in implant use in Kuningan Village. Objective: This study aims to analyze the relationship between myths and husband support on mothers' interest in implant use in Kuningan Village, North Semarang District. Method: This study was an analytical survey with a cross-sectional approach. A total of 89 respondents, consisting of non-MKJP family planning acceptors and those with unmet need, were selected using a cluster sampling technique and proportional random sampling. The research instrument was a questionnaire, and univariate and bivariate data analysis was performed using the chi-square test. Results: The majority of respondents (75.3%) still believed myths, and 56.2% did not receive husband support. The analysis showed a significant relationship between myths (p = 0.003) and husband support (p = 0.010) and mothers' interest in using implants. Conclusion: Myths and husband support significantly influenced mothers' interest in using implants. Perception of myths and the husband's active role in the family planning program were key to mothers' interest in using implants